Designing control systems with controller based on internal model with two degrees of freedom - Ковриго, Юрій Михайлович; Баган, Тарас Григорович; Ущаповський, Андрій Павлович (Eastern-European Journal of Enterprise Technologies, 2014)
In describing complex heat-and-power engineering processes, the vast majority of models has the simplification of behavior of the control object. In practice, it does not allow to set the controller promptly, but only to obtain approximate parameters. Moreover, the control objects in power engineering usually operate in maneuvered regimes, changing the load and internal parameters. The purpose of the research is the synthesis of the controller, which would provide the set-up quality indexes of transient processes, regardless of the model inaccuracy or changes of equipment parameters during operation. The advantages of controller with the internal structure were considered, the stability of the closed - loop system is achieved by selecting stable IC-controller. N∞-norm was taken as the control error estimate. The quality indexes of transient processes in the system with IC-N∞ controller directly depend on one controller parameter, which makes its setting very easy. The resulting structure of the controller may have two degrees of freedom, which improves the quality of transient processes for different control channels, as there is an opportunity to improve the quality of transient processes independently of one another. On the example of ARS of the steam temperature behind upper radiation part of once-through boiler, simulation modeling and comparative analysis of IC controllers with one and two degrees of freedom was carried out. Using the designed controllers allows to ensure sufficient stability margin while maintaining performance and other quality indexes of the regulation system in the entire operating range of loads of the control object.